Made for each other : why dogs and people are perfect partners - Patent, Dorothy Hinshaw (Crown Books for Young Readers, 2018)
Celebrates the bond between humans and their canine companions, discussing scientific insights that demonstrate how sharing one's life with a dog reduces stress, provides companionship, and increases safety.